Do the regional development councils matter in promoting regional development? A historical evidence - Celestino, Alicia B. (2018)
As early as the 1970s, regional development has been adopted by the government as both a goal and strategy for national development. The regional development councils (RDCs) were created to play a critical role in the promotion of regional development. It has been almost five decades since their existence but regional disparities in the country still remain a reality putting to doubt their efficacy. In the light of the federalism debate which enkindled renewed interest in regional development, this article reviews the historical performance of the RDCs to aid policymakers in coming up with policy alternatives to the RDC system. What ails the RDCs? How can they be revitalized? These are some questions central to the assessment of their performance in promoting regional development.
Keywords: Regional planning; Regional economic disparities; Rural development -- Government policy; Decentralization; Regional Development Council (RDC)